Aminothiolation of alkenes with azoles and Bunte salts - Ouyang, Bingqing; Chai, Xing; Li, Zhe; Zhang, Chunling; Liu, Xingmei (Frontiers in Chemistry, 2024)
We have developed an intermolecular aminothiolation of simple olefins using Bunte salt as a thiolating agent. This protocol produces thiyl free radicals under PIDA oxidation conditions, eliminating the need for transition-metal catalysts. The method has a wide range of substrate applicability and is suitable for large-scale preparation and late-stage modification of drug molecules.The simultaneous introduction of sulfur and nitrogen moieties into small molecules is a classical approach for designing new drugs. β-Amino sulfide is an important and widely present scaffold in natural products, bestselling drugs, and small molecular catalysts (Scheme 1A) (Cecchetti et al., 2003;Hosseini-Zare et al., 2011).For a long time, synthetic chemists have devoted considerable effort to develop novel and efficient strategies for the preparation of these significant frameworks (De